If an A.P consists of n terms with first term 'a' and the nth term 'L' show that the sum of mth term from the begining and the mth term from the end is (a+L).

Asked by  | 11th Jan, 2012, 09:05: PM

Expert Answer:

Here, mth term from last = (n-m+1)th term from begining.
Now Sum of mth term from begining and mth term from last
= am + an-m+1
= a + (m - 1)d + a + (n - m + 1 - 1)d
= 2a + (m - 1 +n - m)d
= a + a + (n - 1)d
= a + an
= a + L

Answered by  | 12th Jan, 2012, 09:18: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.